Correlation of Oncotype DX Recurrence Score with Histomorphology and Immunohistochemistry in over 500 Patients. (12th January 2017) - Hanna, Matthew G.; Bleiweiss, Ira J.; Nayak, Anupma; Jaffer, Shabnam
Abstract : Oncotype Dx is used to determine the recurrence risk (RR) in patients with estrogen receptor positive (ER+) and lymph node negative (LN−) breast cancer. The RR is divided into low (0–17), intermediate (18–30), and high (31) to predict chemotherapy benefit. Our goal was to determine the association between histomorphology, immunohistochemistry, and RR. We retrospectively identified 536 patients with ER+ and LN− breast cancers that underwent Oncotype testing from 2006 to 2013. Tumor size ranged from 0.2 cm to 6.5 cm (mean = 1.3 cm) and was uniform in all 3 categories. The carcinomas were as follows: ductal = 63.2%, lobular = 11.1%, and mixed = 35.7%. The RR correlated with the Nottingham grade. Increasing RR was inversely related to PR positivity but directly to Her2 positivity. Of the morphologic parameters, a tubular(lobular) morphology correlated only with low-intermediate scores and anaplastic type with intermediate-high scores. Other morphologies like micropapillary and mucinous were uniformly distributed in each category. Carcinomas with comedo intraductal carcinoma were more likely associated with high RR. Forty-four patients with either isolated tumor cells or micrometastases were evenly distributed amongst the 3 RR. While there was only 1 ER discrepancy between our immunohistochemistry (3+ 80%) and Oncotype, up to 8% of PR+ cases (mean = 15%, median = 5%) and 2% of HER2+ cases were undervalued by Oncotype.